2015
DOI: 10.1089/jir.2014.0159
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Granulocyte Colony-Stimulating Factor and Its Receptor in Skeletal Muscle Is Dependent Upon the Type of Inflammatory Stimulus

Abstract: The cytokine granulocyte colony-stimulating factor (G-CSF) binds to its receptor (G-CSFR) to stimulate hematopoietic stem cell mobilization, myelopoiesis, and the production and activation of neutrophils. In response to exercise-induced muscle damage, G-CSF is increased in circulation and G-CSFR has recently been identified in skeletal muscle cells. While G-CSF/G-CSFR activation mediates pro- and anti-inflammatory responses, our understanding of the role and regulation in the muscle is limited. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…The findings of Wright et al. () are consistent with our findings, and may suggest that resistance exercise does not elicit production of G‐CSF from skeletal muscle. Rather, production of circulating G‐CSF may be a function of systemic inflammation associated with resistance exercise (Roberts ; Wright et al.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of Wright et al. () are consistent with our findings, and may suggest that resistance exercise does not elicit production of G‐CSF from skeletal muscle. Rather, production of circulating G‐CSF may be a function of systemic inflammation associated with resistance exercise (Roberts ; Wright et al.…”
Section: Discussionsupporting
confidence: 92%
“…G-CSF, however, has been demonstrated to increase (Paulsen et al 2005;Wright et al 2015), and remain unchanged (Smith et al 2000;Ross et al 2010) following exercise-induced muscle damage. Exercise volume appears to drive this response as exercise protocols with a greater volume (300 eccentric contractions of knee extensors) being reported to elicit an increase in circulating G-CSF (Paulsen et al 2005;Wright et al 2015), while lower training volumes (~50 eccentric contractions of knee flexors or hip extensors) did not (Smith et al 2000;Ross et al 2010).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in cases of excessive exercise training and inadequate recovery (i.e., overtraining) a disproportionate rise of oxidative stress biomarkers is seen due to the overload of antioxidant system which may be compromised [26,27,28]. It appears that under conditions of elevated oxidant load, ingestion of antioxidant compounds (e.g., thiol-based antioxidants, lipoic acid) [29,30,31,32] and other nutritional supplements [13] may boost antioxidant reserves, help to keep oxidative stress responses under control and lower the inflammatory response. However, it has been suggested that antioxidant reserves, such as reduced glutathione (GSH), may be lower in children, especially those engaged in chronic intensive training programs suggesting that children, and probably adolescents, may be susceptible to exercise-induced oxidative damage [33,34,35].…”
Section: Introductionmentioning
confidence: 99%